Environmental Activism in Indonesian Pesantren: The Role of Lora in Mainstreaming Islamic Eco-theology in Tapal Kuda, East Java - Nor Hasan; Masyithah Mardhatillah; Moh. Mashur Abadi; Ainur Rahman Hidayat (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
Young kiais (also known as lora in Madura culture) at Tapal Kuda, East Java have become increasingly involved in environmental issues, yet not in a fully coordinated or organized manner. This article attempts to give a brief portrayal of this fledgling movement and its moderate form of religious environmentalism. This study seeks to identify the factors responsible for this new environmentalist movement, the individuals behind it, and its impact in East Java. Through interviews and observations it is argued that the lora show moderation in propagating their concerns and empowering the community to take care of the environment as a manifestation of their Islamic eco-theological ethics. The informants responded to internal and external factors described in terms of their typology; participant, proponent, and activator. The movement has a measurable impact in terms of awareness, community establishment, cooperation with relevant institutions and supporting facilities and shows significant potential to develop further and establish itself in the region, while overcoming several challenges that slow its activism. The results of this study are expected to highlight the contributions of what so-called the Islamic eco-theology in Indonesian pesantren that participate in the current efforts to protect and preserve the natural environment.